Publisher Correction: Gas cluster ion beam SEM for imaging of large tissue samples with 10 nm isotropic resolution - Hayworth, Kenneth J.; Peale, David; Januszewski, Michał; Knott, Graham W.; Lu, Zhiyuan; Xu, C. Shan; Hess, Harald F. (Nature methods, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.An amendment to this paper has been published and can be accessed via a link at the top of the paper.